Gender and education in the Paraíba press (1964-1966) (Research, Society and Development, 2020)
This article aims to reflect on women, education and female educators from the mid-1960s Paraiba press. It was intended to analyze the general education panorama of the period and to identify the position and discourses about women in that society, especially the female educators. The desk research, based on the New History perspectives, used as a theoretical contribution the discussions on the use of the press as a historical source and the gender studies. The sources were examined using the mixed method, combining qualitative and quantitative analyzes. From the analysis of the investigated documents, it was possible to have an approximate view of what was Paraiba's education in the 1960s, marked by the expansion of secondary education and the impacts of the military regime. Regarding women, at the same time that they were hardly ever present in the investigated periodical, it was identified the existence of a background debate that questioned the restrictions imposed on the female sex. Female underrepresentation outside spaces traditionally reserved for women was broken by the figure of the female educator. Constant presence in the journals, the female educators, while suffering from the weight of gender stereotypes, were women who freed themselves from the confinement of the domestic home and conquered the public space, engaging in positions of power and standing out as intellectuals. Important figures for the social body, the female educators show the importance of teaching as a strategy for women to penetrate spaces hitherto restricted to the male sex.